Status of indoleamine-2,3-dioxygenase 1 in infiltrating ductal carcinoma of breast cancer: a new prognostic indicator for aggressive tumors - Salmi, T.; Dali-Sahi, M.; Guermouche, B.; Dennouni-Medjati, N.; Hennart, Benjamin; Lenski, Marie; Allorge, Delphine (World cancer research journal, 2021)
The tryptophan pathway has been demonstrated to be involved in tumorprogression. Increased expression of indoleamine 2,3-dioxygenases has been observed in several humantumors types, such as breast cancer. In order to study the role of IDO expression as a prognosticmarker, the serum tryptophan and kynurenine concentrations and the ratio of kynurenine to tryptophan(K/T) of 165 subjects were compared, and correlations were established.